A Rational Designed Novel Bispecific Antibody for the Treatment of GBM - Rui Sun; Yuexian Zhou; Lei Han; Zhidi Pan; Jie Chen; Huifang Zong; Yanlin Bian; Hua Jiang; Baohong Zhang; Jianwei Zhu (Biomedicines, 2021)
Epidermal growth factor receptor variant III (EGFRvIII) is highly and specifically expressed in a subset of lethal glioblastoma (GBM), making the receptor a unique therapeutic target for GBM. Recently, bispecific antibodies (BsAbs) have shown exciting clinical benefits in cancer immunotherapy. Here, we report remarkable results for GBM treatment with a BsAb constructed by the “BAPTS” method. The BsAb was characterized through LC/MS, SEC-HPLC, and SPR. Furthermore, the BsAb was evaluated in vitro for bioactivities through FACS, antigen-dependent T-cell-mediated cytotoxicity, and a cytokine secretion assay, as well as in vivo for antitumor activity and pharmacokinetic (PK) parameters through immunodeficient NOD/SCID and BALB/c mouse models. The results indicated that the EGFRvIII-BsAb eliminated EGFRvIII-positive GBM cells by recruiting and stimulating effector T cells secreting cytotoxic cytokines that killed GBM cells in vitro. The results demonstrated the antitumor potential and long circulation time of EGFRvIII-BsAb in NOD/SCID mice bearing de2–7 subcutaneously heterotopic transplantation tumors and BALB/c mice. In conclusion, our experiments in both in vitro and in vivo have shown the remarkable antitumor activities of EGFRvIII-BsAb, highlighting its potential in clinical applications for the treatment of GBM. Additional merits, including a long circulation time and low immunogenicity, have also made the novel BsAb a promising therapeutic candidate.